Public Expenditure Reviews : Progress and Potential - Swaroop, Vinaya (World Bank, Washington, DC, 2012)
The note reviews the potential of public expenditure reviews as objective analysis of a country's public spending issues, and in advancing the development agenda in the Bank's client countries. It examines the experiences with these reviews, setting the approach for improving them, finding that: most public expenditure reviews define the public sector deficit as the central government deficit, while relevant macroeconomic variables are being ignored; those reviews do not examine the rationale for public intervention, as an analysis on the efficiency of the public budget allocation; do not integrate capital, and recurrent expenditures, thus sidesteps the issue of future recurrent cost implications of the capital budget, introducing uncertainty regarding the sustainability of policies, and projects; and, only a minimal percentage of public expenditure reviews, adequately focus on institutional issues, such as budget management, or incentives in the public sector. The note suggests questioning the exercise of these reviews, as to what will its performance accomplish, and who should participate in the review, followed by a focused process, ensuring ownership, poverty reduction, and information dissemination, to finally build an analysis based on two complementary themes: getting policies right, and building well-functioning institutions to deliver efficient public services.